Statistical description of inhomogeneous samples by scanning microwave microscopy - Monti, Tamara; Udoudo, O.B.; Sperin, Kevin A.; Dodds, Chris; Kingman, S.W.; Jackson, Timothy J. (Institute of Electrical and Electronics Engineers, 2017)
A quantitative analysis of the dielectric properties of a multiphase sample using a scanning microwave microscope (SMM) is proposed. The method is demonstrated using inhomogeneous samples composed of a resin containing micrometric inclusions of a known ceramic material. The SMM suitable for this task employs relatively large tips (tens of micrometers in diameter). Additionally, in order to make the instrument more suitable for high-throughput analysis, an original design for rapid tip changes is implemented. Single-point measurements of dielectric constant at random locations on the sample were performed, leading to histograms of dielectric constant values. These are related to the dielectric constants of the two phases using Maxwell–Garnett effective medium theory, taking into account the volume-of-interaction in the sample beneath the tip.